2014
DOI: 10.1159/000368406
|View full text |Cite
|
Sign up to set email alerts
|

New Strategies for Allergen T Cell Epitope Identification: Going beyond IgE

Abstract: Background: Type I allergy and allergic asthma are common diseases in the developed world associated with IgE antibodies and Th2 cell reactivity. To date, the only causative treatment for allergic disease is specific immunotherapy (SIT). Method: Here, we review recent works from our laboratory focused on identifying human T cell epitopes associated with allergic disease and their potential use as biomarkers or therapeutic targets for SIT. In previous studies, we have mapped T cell epitopes associated with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Alongside the well-studied IgE-mediated allergic reaction ( 24 ), T cell reactivity and recognition of allergen T cell epitopes also plays an important role in the sensitization and potentiation of allergic reactions ( 16 , 26 29 ). Small peptides in the urine are potentially volatile and could be adsorbed through the nose and mucosal surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Alongside the well-studied IgE-mediated allergic reaction ( 24 ), T cell reactivity and recognition of allergen T cell epitopes also plays an important role in the sensitization and potentiation of allergic reactions ( 16 , 26 29 ). Small peptides in the urine are potentially volatile and could be adsorbed through the nose and mucosal surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Characterization of the profile of epitopes from a specific allergen source recognized by T cells may help in understanding the dynamics of the allergic immune response and identifying biomarkers or therapeutic targets for specific immunotherapy. In an immunoproteomics approach, Schulten et al [51] found a surprisingly high proportion of T H 2 cell recognition of peptides from non-IgE-binding timothy grass proteins in grass pollen allergic patients. Moreover, recognition of some of those novel T-cell antigens correlated with outcomes of grass pollen-specific immunotherapy.…”
Section: Allergen Databasesmentioning
confidence: 99%
“…MHC class II molecules are encoded by three different loci, designated HLA DR, DQ, and DP. Each of these three loci is extremely polymorphic adding a high degree of complexity, which has to be accounted for in the design of T cell epitope mapping strategies [21].…”
Section: Challenges Of T Cell Epitope Mappingmentioning
confidence: 99%